Review of the genus Diduga Moore (Lepidoptera, Erebidae, Arctiinae) of Taiwan, with descriptions of two new species - Bayarsaikhan, Ulziijargal; Heppner, John B.; Kwon, Hyung-Wook; Bae, Yang-Seop (Zootaxa, 2021)
Two new species, Diduga taiwana sp. n. and D.nantouensis sp. n. are described from Taiwan. Illustrations of adults and genitalia of examined species from Taiwan are given.